Vliv sirovodíkového působení na cytokinové receptory psoriatických keratinocytů - Arenberger, Petr; Schwarz, I (Československá dermatologie, 1997)
Balneotherapy is a modern and perspective method of treatment of some skin diseases. Enhanced proliferation of epidermal cells in psoriatic plaques can be influenced by many different procedures. The objective of the present work was to evaluate in vivo the effect of hydrogen sulphide water, which is used for balneotherapeutic procedures in 10 patients with chronic stationary psoriasis vulgaris. The authors investigated the receptor characteristics at keratinocytic binding sites in psoriatic plaques before the balneotherapeutic application of hydrogen sulphide water and after its termination. They found that this method of balneotherapy reduces the pathologically enlarged number of receptors for the epidermal growth factor on keratinocytes to a level which corresponds to findings in normal subjects. The described experiments can contribute to the explanation of favourable therapeutic effects of hydrogen sulphide water on reduced hyperproliferation of keratinocytes in the psoriatic epidermis and thus have a favourable effect on psoriatic changes.
Keywords: dospělí; balneologie; keratinocyty; Female; Receptors, Growth Factor; psoriáza; Keratinocytes; Adult; sulfan; ženské pohlaví; receptory růstových faktorů; lidé; Balneology; Hydrogen Sulfide; Male; lidé středního věku; mužské pohlaví; Psoriasis; Middle Aged; Humans